EFFECT OF TEMPERATURE ON OXYGEN CONSUMPTION AND AMMONIA EXCRETION IN EARTHWORM Libyodrilus violaceus (BEDDARD) - Melefa, Temitope Dadewura; Owa, Stephen Olugbemiga (FUDMA JOURNAL OF SCIENCES, 2023)
Libyodrilus violaceus, an Oligochate of the family Eudrilidae is a species of earthworm found in West Africa. To comprehend how organisms function physiologically, the knowledge of their metabolism is essential. In this present study, the effect of temperature on oxygen consumption and ammonia excretion in this earthworm was studied. Oxygen consumption and ammonia excretion were measured at different temperatures and at different body mass groups. The results obtained show that small sized earthworms produce more ammonia per gram body mass than the large-sized earthworms. This implies that small sized earthworms or juveniles will better convert organic materials into vermicompost than the large sized worms or adult worms. Also, at higher and lower temperatures the earthworms produce more ammonia and consume less oxygen, this could lead to injury and even death of the earthworms. This suggests that temperature could be a limiting factor in vermicoposting and vermiculture. In addition to providing basic data on the ecophysiology of Libyodrilus violaceus, the results from this study give some information that may be useful in vermiculture and vermcomposting. Since small sized worms produce more ammonia than adult or larger sized worm, efforts should be made in rearing more juvenile worms in vermiculture that will be useful in vermicompost since their physiological activities depend on their intake.